Lead-Free Solder Alloy

A lead-free solder alloy composed of Sn-Cu with added elements like Co, Mn, Pd, Rh, and Fe replicates the performance of nickel-containing alloys, addressing the safety concerns of nickel and enhancing the reliability and applicability of lead-free soldering.

JP7649043B2Active Publication Date: 2025-03-19NIHON SUPERIOR CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021545632
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-12
Filing Date
2020-09-11
Publication Date
2025-03-19
Estimated Expiration
2040-09-11

AI Technical Summary

Technical Problem

Current lead-free solder alloys, such as Sn-Cu-Ni, contain nickel which is a skin sensitizer, limiting their use in consumer products despite their excellent solderability and bonding reliability.

Method used

Developing a lead-free solder alloy with a basic composition of Sn-Cu and incorporating one or more elements such as Co, Mn, Pd, Rh, and Fe to replicate the solderability and bonding reliability of nickel-added alloys without using nickel.

Benefits of technology

The resulting solder alloy achieves equivalent or superior solderability, mechanical strength, and bonding reliability to nickel-containing alloys while being free of nickel, thus ensuring safety and wider applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649043000003
    Figure 0007649043000003
  • Figure 0007649043000004
    Figure 0007649043000004
  • Figure 0007649043000005
    Figure 0007649043000005
Patent Text Reader

Abstract

The purpose of the present invention is to provide a lead-free solder alloy and a solder bonded body that, despite no addition of "Ni", have solderability and bonding characteristics as with a "Ni"-added lead-free solder alloy. This lead-free solder alloy is characterized in that Sn-Cu is used as a basic composition and that the basic composition contains one or more selected from the group consisting of Co, Mn, Pd, Rh, and Fe. By using the lead-free solder alloy, it is possible to achieve: a lead-free solder alloy that, as compared with a "Ni"-containing lead-free solder, is free from Ni sensitization, and exhibits excellent solderability and workability during soldering and excellent mechanical characteristics and bonding reliability; and a solder bonded body using the lead-free solder alloy.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lead-free solder alloy having excellent soldering characteristics and long-term reliability, and to a soldered joint using said alloy. [Background technology]

[0002] To reduce the burden on the global environment, lead-free solder is widely used as a joining material for electronic components, and typical compositions for this include Sn-Ag-Cu solder alloys and Sn-Cu-Ni solder alloys. In recent years, Sn-Cu-Ni solder alloys have been rapidly gaining popularity in the market due to their excellent properties, such as high mechanical strength, stable joint strength against thermal history and impact, high fluidity and good mountability, as well as their cost advantage over Sn-Ag-Cu solder.

[0003] However, Sn-Cu-Ni solder alloys contain trace amounts of "Ni," which is known to be a skin sensitizer. On the other hand, "Ni" is also contained in 500 yen coins, and is an element found in environments where many people have the opportunity to touch it with their bare hands. Lead-free solder is widely used as a joining material in the manufacture of electronic components and devices, but currently it is used in extremely limited environments compared to 500 yen coins, which are often touched by the general public. Companies are being called upon to provide safer products that do not contain skin sensitizers.

[0004] Incidentally, many benefits are known regarding the effect of adding "Ni" to lead-free solder. In particular, Patent Document 1 discloses that the addition of "Ni" improves the fluidity of lead-free solder alloys whose main component is Sn-Cu. Furthermore, the effect of adding "Ni" is that (Cu,Ni) is formed at the bonding interface with the copper substrate as disclosed in Patent Document 2. 6 Sn 5 It is known that the formation of an intermetallic compound (IMC) with the above composition results in excellent mechanical properties and joint reliability.

[0005] Therefore, there is a demand for a lead-free solder alloy composition that does not contain "Ni" but has the same excellent solderability and joint reliability as those containing "Ni." [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 3152945 [Patent Document 2] International Publication No. 2009-051255 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a lead-free solder alloy and a solder joint that have the same solderability and joint reliability as those containing "Ni" even though they do not contain "Ni". [Means for solving the problem]

[0008] The inventors conducted extensive research into elements that could be used to replace "Ni" in Sn-Cu based lead-free solder alloys and discovered that Co, Mn, Pd, Rh, and Fe have solderability and joint reliability similar to that of lead-free solder alloys to which "Ni" has been added, thereby completing the present invention.

[0009] That is, the present invention relates to a lead-free solder alloy having a basic composition of Sn-Cu and containing one or more elements selected from the group consisting of Co, Mn, Pd, Rh and Fe, and a solder joint using the lead-free solder alloy. Effect of the Invention

[0010] The present invention is a solder alloy that does not contain "Ni" but has solderability and high joint reliability equal to or better than that of lead-free solder alloys that contain "Ni". Therefore, it is a solder alloy that can be used for soldering a wide range of electronic components and electronic devices, and has a high level of safety with minimal impact on the human body. [Brief description of the drawings]

[0011] [Figure 1] Graph comparing zero crossing times [Diagram 2] SEM photo of Example 2 [Diagram 3] SEM photo of Comparative Example 1 [Figure 4] SEM photo of Comparative Example 2 [Diagram 5] Photograph of solidified sample in Example 2 [Figure 6] Photo of solidified sample of Comparative Example 1 [Figure 7] Photo of solidified sample of Comparative Example 2 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. The lead-free solder alloy of the present invention is a lead-free solder alloy having a basic composition of Sn-Cu and containing one or more elements selected from the group consisting of Co, Mn, Pd, Rh and Fe, and a solder joint using the lead-free solder alloy. Furthermore, by including Ge, Ga, P, Si, Al, V, and Zr, which have an antioxidant effect, the solderability and workability during soldering are further improved.

[0013] It is known that Sn-Cu based lead-free solder alloys with added "Ni" have excellent mounting performance, such as stable joint strength and excellent solderability. The reason for this is the (Cu, Ni) 6 Sn 5 These include the formation of IMCs and the refinement of IMC particles. Cu in Sn-Cu solder alloys6 Sn 5 It is known that at 186°C, the stable crystal structures are monoclinic (hereafter referred to as η' phase) and hexagonal (hereafter referred to as η phase), and that the phase transforms to the more stable crystal structure depending on the environmental temperature. Furthermore, it is known that the volume change of the crystal during phase transformation can lead to the accumulation of stress and strain inside the crystal, which can lead to the generation of cracks. On the other hand, it is formed in Sn-Cu solder alloys with added "Ni" (Cu, Ni). 6 Sn 5 Since only the η phase exists, the above-mentioned phase transformation does not occur, and therefore accumulation of stress strain inside the crystal and generation of cracks do not occur, making it possible to maintain a stable bonded state. In addition, finely divided (Cu, Ni) 6 Sn 5 The IMC particles disperse and strengthen the solder alloy, improving its mechanical strength. These excellent properties prevent a decrease in bond strength even when exposed to heat cycles that involve continuous exposure to hot and cold environments, or to changes in the temperature environment such as aging caused by long periods of exposure to high temperatures, resulting in the effect of maintaining a stable bond for a longer period of time.

[0014] Furthermore, the addition of "Ni" improves the fluidity of the solder alloy. Improved fluidity is a very important characteristic in terms of improving mountability. If the fluidity decreases, needle-like crystals will form, and bridges that short out conductors will form, or protruding horns will form when the board with electronic components attached separates from the molten layer, resulting in poor quality. Also, if the wettability of the solder alloy to the base material or electronic components decreases, the through-hole ripping will deteriorate, resulting in poor quality. Products that experience bridges, horns, or poor through-hole ripping will be rejected as defective products during mounting, reducing yield. Deterioration of mountability has a significant impact on the efficiency of mass production work.

[0015] In the present invention, in order to obtain the same characteristics as when "Ni" is added, Co, Pd, Rh, Mn, and Fe are selected as elements that can be substituted for "Ni". The selected elements have the effect of refining IMC particles, similar to the effect of "Ni".

[0016] It is known that the mechanical strength of Sn-Cu based lead-free solder alloys with the addition of "Ni" is improved. Comparing the SEM images of the solder alloy with the addition of "Ni" in Figure 2 and the solder alloy with the addition of Co in Figure 3, the IMC particles are elliptical in shape, with the largest measuring approximately 1.2 μm in major axis and approximately 0.8 μm in minor axis, and IMCs of the same shape and dimensions are formed at the joint interface. It can be seen that the IMCs in the solder alloy with the addition of Co are finer, just like in the case of the addition of "Ni," and even the shape and dimensions are the same. On the other hand, the fact that the IMC particles in the solder alloy with the addition of Co are finer and the shape and dimensions of the IMC particles are the same as those in the solder alloy with the addition of "Ni" means that the mechanical strength of the solder alloy with the addition of Co is also improved. The IMC formed at the joint interface is known to be harder and more brittle than the solder alloy. Because the linear expansion coefficients of the IMC, board, and electronic components are different, thermal shock generates stress, and if the stress is uneven, cracks form in the IMC, destroying the IMC in the brittle parts and compromising the joint reliability of the solder alloy. By suppressing the growth of the IMC and miniaturizing it, a highly reliable solder alloy with stable joint strength that can withstand stress can be obtained.

[0017] Like Ni and Co, the addition of Pd, Rh, Mn, and Fe, elements that refine IMC particles, to a solder alloy will form IMCs of the same shape as when Ni is added, which is expected to result in a solder alloy with improved mechanical strength and stable joint strength and high reliability.

[0018] Next, in order to compare the fluidity that affects the mounting property of the solder alloys, the wettability as an index was measured and compared. The wettability of the solder alloys in which "Ni" was replaced with other elements as shown in Table 2 and FIG. 1 was measured, and the results showed that the wettability was improved compared to the solder alloy to which "Ni" was added. In particular, the solder alloy to which Co was added had a value of 90 to 94% compared to Comparative Example 1 to which "Ni" was added, and it was found to have an excellent effect of improving wettability compared to Pd, Rh, Mn, and Fe. From the results of the wettability measurement, it was found that the solder alloy of the present invention has improved fluidity, suppresses the occurrence of bridges and horns, and improves through-hole rising, making it a solder alloy with excellent mounting property.

[0019] The lead-free solder alloy of the present invention is characterized in that it has a basic composition of Sn and Cu, and further contains one or more elements selected from the group consisting of Co, Mn, Pd, Rh and Fe. The Cu content is preferably from 0.1 to 1.0 mass %, more preferably from 0.5 to 0.9 mass %. The Co content is preferably from 0.001 to 0.1 mass %, and more preferably from 0.01 to 0.05 mass %. The Mn content is preferably from 0.001 to 0.01 mass %, and more preferably from 0.003 to 0.008 mass %. The Pd content is preferably from 0.01 to 1.0 mass %, and more preferably from 0.04 to 0.1 mass %. The Rh content is preferably from 0.005 to 0.5% by mass, and more preferably from 0.01 to 0.1% by mass. The Fe content is preferably from 0.001 to 0.01 mass %, and more preferably from 0.003 to 0.008 mass %. The Sn content is other than the above elements and unavoidable impurities. Among the "Ni" substituting elements Co, Mn, Pd, Rh, and Fe, Co is preferred.

[0020] In addition, examples of elements having an antioxidant effect that can be added to the lead-free solder alloy of the present invention include one or more elements selected from the group consisting of Ge, Ga, P, Si, Al, V, and Zr. There are no particular restrictions on the content of these elements as long as they provide the effects of the present invention, but the following contents are preferred. The Ge content is preferably from 0.0001 to 0.1 mass %, and more preferably from 0.005 to 0.01 mass %. The Ga content is preferably from 0.0001 to 0.1 mass %, and more preferably from 0.003 to 0.008 mass %. The P content is preferably from 0.0001 to 0.1 mass %, and more preferably from 0.003 to 0.005 mass %. The Si content is preferably from 0.0001 to 0.1 mass %, and more preferably from 0.005 to 0.01 mass %. The Al content is preferably from 0.0001 to 0.05 mass %, and more preferably from 0.003 to 0.008 mass %. The V content is preferably from 0.0001 to 0.05 mass %, and more preferably from 0.005 to 0.01 mass %. The Zr content is preferably from 0.0001 to 0.05 mass %, and more preferably from 0.005 to 0.01 mass %.

[0021] The lead-free solder alloy of the present invention is characterized in that it contains Sn and Cu as a basic composition, and further contains one or more elements selected from the group consisting of Co, Mn, Pd, Rh, and Fe, Furthermore, by adding one or more elements selected from the group consisting of Ge, Ga, P, Si, Al, V, and Zr as elements having an antioxidant effect, it is possible to obtain excellent soldering characteristics and high joint reliability, but Ag, Sb, Bi, In, Zn, Ti, etc. can also be added within the range that provides the effects of the present invention. In addition, the shape can be processed as desired depending on the application. For example, when soldering is performed by dip soldering, the solder can be processed into a rod-like solder shape; when soldering is performed by reflow soldering, the solder can be processed into a paste, ball, or preform shape; and when soldering is performed using a soldering iron, the solder can be processed into a wire shape such as resin-cored solder. EXAMPLES

[0022] The present invention will now be described in more detail with reference to examples. (Wettability evaluation) In order to verify the effect of the present invention, a wettability evaluation was carried out. [Evaluation Sample] Evaluation sample: Solder alloy with the composition shown in Table 1

[0023] [Table 1]

[0024] [Evaluation method] In accordance with JIS Z3197:2012 "Wetting balance method", the solder alloys of Examples 1 to 25 and Comparative Examples 1 to 3, standard flux B, and phosphorus deoxidized copper plate (thickness: 0.3 mm, width: 10 mm, length: 30 mm) were prepared, and measurements were performed using a Rhesca Solder Checker (SAT-5100) under the following conditions: immersion depth: 2 mm, immersion speed: 20 mm / sec, immersion time: 10 sec, and solder bath temperature: 35±3°C (in accordance with JIS) from the liquidus temperature. The results are shown in Table 2 and FIG. The evaluations shown in Table 2 and FIG. 1 show the values ​​for Examples 1 to 25 and Comparative Examples 2 and 3, with the zero cross time and the zero cross time of Comparative Example 1 taken as 100%.

[0025] [Table 2]

[0026] 1, all samples in Examples 1 to 25 showed values ​​below 100%, and were found to have superior wettability compared to Comparative Example 1, which added "Ni" that has a wettability improving effect. Among them, Examples 2, 6 to 8, 9, 12, 17, and 20 to 22, which contained Co, showed values ​​of 90 to 94%, which is smaller than the 94 to 98% of the Examples in which other elements were added, and it is clear that the effect of improving wettability is high.

[0027] Furthermore, in Examples 6 to 25, one or more of the following elements having an antioxidant effect were contained: 0.0001 to 0.1 mass% Ge, 0.0001 to 0.1 mass% Ga, 0.0001 to 0.1 mass% P, 0.0001 to 0.1 mass% Si, 0.0001 to 0.05 mass% Al, 0.0001 to 0.05 mass% V, and 0.0001 to 0.05 mass% Zr. The zero cross times of Examples 6 to 25 were all shorter than that of Comparative Example 1, and it was found that the inclusion of an element having an antioxidant effect did not inhibit wettability, and that the element that refines the particles of the intermetallic compound was effective.

[0028] From the results shown in Table 2 and FIG. 1, it was found that all of the examples of the present invention were superior in wettability compared to Comparative Example 1 in which "Ni" was added. In addition, when the state of the samples when melted was visually observed, it was confirmed that Examples 1 to 25 were comparable to Comparative Example 1 in terms of fluidity.

[0029] (Evaluation of bonding condition) In order to evaluate the bonding state, the copper plates (phosphorus deoxidized copper plates) of Example 2, Comparative Example 1, and Comparative Example 2, which had been evaluated for wettability, were subjected to a surface etching treatment, and the surfaces were observed. [Method of preparing observation samples] The soldered surface of the copper plate for which wettability was evaluated was immersed for approximately 5 minutes in a mixed solution of sodium hydroxide solution (concentration: 50 g / L) and orthonitrophenol solution (concentration: 35 g / L) heated to approximately 60°C, then polished with a cotton swab, washed with running water, and air-dried to prepare the observation sample. [Observation method] The specimen was observed and evaluated at a magnification of 7000 times using a scanning electron microscope (JSM-6360LA) manufactured by JEOL Ltd.

[0030] 2 to 4, comparing the IMC particles formed at the joint interface in Example 2 and Comparative Example 1, both have an elliptical shape, with the largest particle size being about 1.2 μm in major axis and 0.8 μm in minor axis, and IMCs of the same shape and dimensions are formed at the joint interface. It can be seen that the solder alloy to which Co is added has fine IMCs, just like the solder alloy to which "Ni" is added, and furthermore, the shape and dimensions are the same. However, in Comparative Example 2, which did not contain Ni or Co, the shape was closer to circular compared to Example 2 and Comparative Example 1, and the diameter of the IMC particle size was as large as about 2.0 μm, which was approximately twice as large as in Example 2 and Comparative Example 1, which contained "Ni."

[0031] It is known that the mechanical strength of Sn-Cu based lead-free solder alloys with the addition of "Ni" is improved. The fact that the IMC particles of the solder alloy with the addition of Co are finer and the shape and dimensions of the IMC particles are the same as those of the solder alloy with the addition of "Ni" indicates that the mechanical strength of the solder alloy with the addition of Co is also improved. In addition, the IMC formed at the joint interface is known to be harder and more brittle than the solder alloy. Because the linear expansion coefficients of the IMC, board, and electronic components are different, thermal shock generates stress, and if the stress is uneven, cracks form in the IMC, destroying the IMC in the brittle parts and compromising the joint reliability of the solder alloy. By suppressing the growth of the IMC and miniaturizing it, a highly reliable solder alloy with stable joint strength that can withstand stress can be obtained. Like Ni and Co, the addition of Pd, Rh, Mn, and Fe, elements that refine IMC particles, to a solder alloy forms IMCs of the same shape as when Ni is added, which is expected to result in a solder alloy with improved mechanical strength and stable joint strength and high reliability.

[0032] In other words, the SEM photographs in Figs. 2 to 4 show that the lead-free solder alloy of the present invention, which has a composition based on Sn-Cu in Example 2 and contains Co, is a highly reliable solder alloy with improved mechanical strength and stable joint strength, similar to Comparative Example 1, which has a conventional composition containing "Ni." Similarly, the elements Mn, Pd, Rh, and Fe also refine the IMC particles, so the IMC particles formed by adding Mn, Pd, Rh, and Fe have the effect of improving the mechanical strength of the solder alloy and stabilizing the joint strength, and it is presumed that solder alloys with Mn, Pd, Rh, and Fe added are highly reliable solder alloys.

[0033] (Solderability evaluation) Next, the results of a solidification test of the lead-free solder alloy of the present invention will be described. [Coagulation test method] Approximately 50 g of the solder alloy sample was weighed out and melted at 270° C., after which approximately 40 g was poured into a mold and allowed to cool at room temperature to obtain a solidified sample. [Coagulation test evaluation method and results] The evaluation was performed by visually checking the surface gloss and the presence or absence of shrinkage cavities. FIG. 5, which is a solidified sample of Example 2 of the present invention, and FIG. 6, which is a solidified sample of Comparative Example 1 containing "Ni", each have excellent surface gloss and no shrinkage cavities are observed, whereas FIG. 7, which is Comparative Example 2 containing no Co, has a surface gloss but has shrinkage cavities in the center of the solidified sample. The addition of "Ni" results in excellent surface gloss and prevents shrinkage cavities. Similar effects are seen in Example 2, in which Co is added. This proves that Co, a component of the lead-free solder alloy of the present invention, has a substitution effect for "Ni." [Industrial Applicability]

[0034] The present invention is capable of providing solder joints that are equal to or better than those of lead-free solder alloys that contain "Ni," in terms of solderability, workability during soldering, mechanical properties, and joint reliability, even though it does not contain any "Ni." This makes it possible to expect the present invention to be widely applied to the joining of electronic devices, electronic components, etc.

Claims

1. A lead-free solder alloy which does not contain Ag, and has a basic composition of Sn and Cu, with one or more elements selected from the group consisting of Co, Rh and Fe, with the respective contents being as follows: Cu content of 0.1 to 1.0 mass%, Co content of 0.001 to less than 0.005 mass%, Rh content of 0.005 to 0.5 mass%, Fe content of 0.001 to less than 0.005 mass%, with the remainder consisting of unavoidable impurities and Sn.

2. The lead-free solder alloy according to claim 1, characterized in that it contains one or more elements selected from the group consisting of Ge, Ga, P, Si, Al, V and Zr as elements having an antioxidant effect, and the respective contents thereof are as follows: Ge content is 0.0001 to 0.1 mass%, Ga content is 0.0001 to 0.1 mass%, P content is 0.0001 to 0.1 mass%, Si content is 0.0001 to 0.1 mass%, Al content is 0.0001 to 0.05 mass%, V content is 0.0001 to 0.05 mass%, and Zr content is 0.0001 to 0.05 mass%.

3. A soldered joint, characterized in that the soldered joint is made using the lead-free solder alloy according to claim 1 or 2.

Citation Information

Patent Citations

  • Lead-free solder alloy

    JP2003001482A

  • Solder alloy

    JP2006061914A

  • Solder alloy

    JP2007038228A

  • Solder alloy, solder ball, chip solder, solder paste and solder joint

    JP2018167310A

  • Lead-free solder alloy

    JP3152945B2